Modulating electrochemical redox behavior of semiconductive polymers on soft and stretchable substrates and methods of use

By adjusting the oxygen permeability of the stretchable substrate and forming a stretchable redox active layer, the inherent stretchable OECT performance is solved, and the high on/off ratio and mobility is improved. It is suitable for electronic skin, soft implants, and soft neuromorphic calculations.

CN119605341APending Publication Date: 2025-03-11THE UNIVERSITY OF HONG KONG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380050717.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-28
Filing Date
2023-06-17
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The performance of inherent stretchable organic electrochemical transistors (OECTs) remains lower than that of rigid devices, especially in terms of on/off ratios and charge carrier mobility.

Method used

The electrochemical and electrochromic properties as well as nonlinear and synaptic behavior of organic electrochemical devices are adjusted by changing the oxygen permeability of the stretchable substrate. A specific method is to select a stretchable substrate with low oxygen permeability and form a stretchable redox active layer thereon, including conductive polymers, organic molecules or organic-inorganic hybrid molecules.

Benefits of technology

The OECT's on/off ratio was significantly improved from about 10 to about 104, and the mobility was improved to about 1.1 cm2 V-1s-1, and the device still operated normally after 0% to 50% cyclic strain test.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119605341A_ABST
    Figure CN119605341A_ABST
Patent Text Reader

Abstract

An intrinsic stretchable organic electrochemical crystal (OECT) having overall performance comparable to that of a rigid device. The high performance is achieved by reducing the oxygen permeation rate (PO2) of the stretchable substrate, which is beneficial to the dedoping process of the conductive polymer channel. The high performance inherently stretchable OECT may not only be used in the field of soft bioelectronics and facilitate new device paradigms of tissue-like stretchable OECTs in the fields of epidermal biosensing, flexible neuromorphic calculations, soft human-computer interfaces, and the like, but also be used to reveal new key parameters to alter the performance of devices based on stretchable conductive polymers.
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims priority to U.S. Provisional Patent Application Serial No. 63 / 367,160 filed on June 28, 2022, and the disclosure of the U.S. Provisional Patent Application is incorporated by reference in its entirety. Technical Field

[0002] The present invention relates to a method for modifying the electrochemical behavior of conductive polymers and devices made of conductive polymers on soft and stretchable substrates. More specifically, the present invention introduces a stretchable device equipped with an intrinsically stretchable organic electrochemical transistor modified by the above method, and the intrinsically stretchable organic electrochemical transistor shows performance comparable to that of a rigid device. Background Art

[0003] Organic electrochemical devices based on semiconducting polymer films stand out due to their working mechanisms, which are very similar to real neurons, both organic, ion signaling, and electrochemically operated. To further promote the application of organic synapses in soft biointerfaces, stretchable devices have been proposed to minimize the mechanical mismatch. The main challenge in developing stretchable organic electrochemical devices is the need to systematically reconstruct the material system and the fabrication method.

[0004] For example, in 2017, Zhang et al. reported the first fully stretchable organic electrochemical transistor (OECT) on an elastic polydimethylsiloxane (PDMS) substrate [1]. The device was fabricated using a buckling method and solid hydrogel as a stretchable electrolyte. A 10×10 stretchable OECT array was demonstrated. The stretchable OECT can withstand up to 30% strain with stable performance. In 2018, Ramuz et al. reported stretchable OECTs patterned with stretchable serpentine electrodes and channels using a laser etching method [2]. The device can maintain a high transconductance of 0.35 mS at 38% strain. In 2018, Lee et al. fabricated a stretchable OECT with a stretchable nanomesh architecture [3]. The device was used for conformal electrocardiographic recording in living rats. In 2019, Zhang et al. reported the first intrinsically stretchable OECT using ultrathin microcracked gold films as stretchable interconnects and microcracked PEDOT:PSS films as stretchable channels [4]. Matsuhisa et al. reported the use of intrinsically stretchable OECTs to fabricate intrinsically stretchable synaptic transistors [5]. In 2019, Li et al. reported stretchable OECTs for glucose detection [6]. The stretchable OECT sensor maintained its sensing function between 0% and 30% strain. In 2021, Nguyen et al. demonstrated artificial synapses with stretchable OECTs, where synaptic enhancement could be controlled by regulating the kinetics of ion transport [7].

[0005] Despite the above achievements in advancing stretchable OECTs, the performance of intrinsically stretchable OECTs is still quite low compared to their rigid counterparts. For example, the on / off ratio of intrinsically stretchable OECTs fabricated on stretchable substrates such as PDMS is two orders of magnitude lower than that of rigid devices. In addition, the charge carrier mobility of stretchable OECTs remains to be studied. Recent work has focused on addressing these issues, including the introduction of a buffer layer between the substrate and the channel material and the use of different substrate materials. However, there has been limited progress in identifying the key parameters that lead to this phenomenon. Therefore, there is a need to elucidate the underlying mechanism and provide guidance for future device design. Summary of the invention

[0006] Therefore, this paper provides a method to tune the electrochemical and electrochromic properties as well as nonlinear and synaptic behaviors of organic electrochemical devices by changing a key parameter (oxygen permeability of a stretchable substrate) that significantly affects the redox behavior in semiconductors. Taking stretchable OECTs as an example, by adopting a stretchable substrate with low oxygen permeability, the on / off ratio is improved from about 10 to a value of about 10 4 , where the high mobility is about 1.1 cm 2 V -1 s -1In addition, the devices still function normally even after cyclic strain testing between 0% and 50%. These devices show high mobility comparable to that of rigid devices and have potential applications such as electronic skin, soft implants, and soft neuromorphic computing.

[0007] On the one hand, a method for changing the electrochemical properties, electrochromic properties, nonlinearity and synaptic behavior of an electronic device by providing a stretchable substrate selected from one or more of an elastomer, a hydrogel or an organic-inorganic hybrid material, wherein the stretchable substrate has a selected oxygen permeability of 0.1 to 50 Barrer; and forming a stretchable redox active layer on the substrate, wherein the redox active layer includes one or more of a conductive polymer, an organic molecule or an organic-inorganic hybrid molecule.

[0008] In one embodiment, the ratio of poly(3,4-ethylenedioxythiophene) to poly(styrene-sulfonic acid) in the mixture forming the electrodes and the channels is 1:1 to 1:3.

[0009] In another embodiment, the method further comprises depositing one or more electrodes on the elastic redox active layer.

[0010] In yet another embodiment, the electronic device is a bioelectronic device in the form of a bioelectrode, a wearable biosensor, or a bioelectronic implant.

[0011] In other embodiments, the electronic device has the shape of a microwire, a macrowire, a micromesh, a macromesh, a film, a micro 3D structure, and / or a macro 3D structure.

[0012] In yet other embodiments, the stretchable substrate is selected from styrene-butadiene rubber, ethylene propylene diene monomer, poly(styrene-ethylene-butylene-styrene), ethylene vinyl acrylate and / or thermoplastic polyurethane.

[0013] In another aspect, a stretchable device equipped with an intrinsically stretchable organic electrochemical transistor is provided. The device comprises an OECT, the OECT comprising a stretchable planar gate electrode, a source electrode, a drain electrode and a channel each comprising a conductive polymer; a stretchable ion gel, the stretchable ion gel being cast on the channel and the gate as a solid electrolyte; and a stretchable elastomeric substrate. The OECT has a width / length ratio of 3.5 to 50; an on / off ratio of the device of at least 10 3 ; The mobility of the device is at least 0.8cm 2 V -1 s -1 ; and when the device is stretched to 150% of its original length, the current loss of the transistor is less than 10%.

[0014] In one embodiment, the stretchable substrate is selected from an elastomer, a hydrogel or an organic-inorganic hybrid stretchable polymer.

[0015] In a further embodiment, the stretchable substrate is selected from styrene-butadiene rubber, ethylene propylene diene monomer, poly(styrene-ethylene-butylene-styrene), ethylene vinyl acrylate and / or thermoplastic polyurethane.

[0016] In other embodiments, the device has the shape of a microwire, a macrowire, a micromesh, a macromesh, a membrane, a micro 3D structure, and / or a macro 3D structure.

[0017] In one embodiment, the conductive polymer is a mixture of poly(3,4-ethylenedioxythiophene) and poly(styrene-sulfonic acid).

[0018] In another embodiment, the ratio of the poly(3,4-ethylenedioxythiophene) to the poly(styrene-sulfonic acid) is 1:1 to 1:3.

[0019] In another embodiment, the stretchable ion gel is a polyacrylamide based gel.

[0020] In yet other embodiments, the mobility of the transistor decreases by less than 10% when the device is stretched to 110% of its original length.

[0021] In yet another embodiment, the mobility of the transistor decreases by less than 25% when the device is stretched to 150% of its original length. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figures 1A to 1D The results show that the O2 ) on a substrate with intrinsically stretchable properties. Figure 1A Shown is the structure of an OECT based on a conducting polymer PEDOT:PSS channel. Figure 1B Schematic diagram of the intrinsically stretchable OECT. Figure 1C Transfer curves of intrinsically stretchable OECTs fabricated on PDMS substrates with different mixing ratios are shown. Figure 1D The on / off ratio of the device and the oxygen permeability of the substrate (P O2 ) graph.

[0023] Figures 2A to 2C To compare the O2 Values ​​of the on / off ratios of stretchable OECTs fabricated on different types of stretchable substrates. Figure 2A The chemical structures of different stretchable substrates are shown. Figure 2B Transfer curves of stretchable OECTs fabricated on various substrates are shown. Figure 2C The on / off ratio of the device is shown versus the P of the corresponding substrate. O2 The correlation between the values.

[0024] Figures 3A to 3F For low P O2 The overall performance of intrinsically stretchable OECTs on substrates is benchmarked against rigid OECTs on glass. Figure 3A shows the output curve where V ds Sweep from 0V to -0.6V, and V g The voltage was scanned from 0 V to 0.8 V in 0.2 V steps. Figure 3B shows the transfer curve, where V ds is fixed at -0.4V, and V g Sweep from 0V to 0.8V. Figure 3C The on / off ratios of intrinsically stretchable OECTs and rigid OECTs with different geometries (width-to-length ratio, W / L) are shown. Figure 3D shows the transient response curve, where a 0.4V V g pulse, and V ds Fixed at -0.2V. Figure 3E shows the frequency response curve of gm, where V ds Fixed at -0.4V, and a 20mV small signal oscillation is superimposed on the 0.1V constant V g To measure the transient g m . Figure 3F The intrinsically stretchable OECTs respond from 0.05 Hz to 10 4 Hz triangle wave input output I ds .

[0025] Figures 4A to 4E The performance of intrinsically stretchable OECTs under strain is presented. Figure 4A The architecture of an intrinsically stretchable OECT is shown, where PEDOT:PSS films serve as electrodes (source, drain, and gate) and the channel. Figure 4B shows the transient curves at different strain values, where V g sweeps from 0V to 0.9V, and V ds Fixed at -0.4V. Figure 4C Transfer curves after different strain cycles (50% strain) are shown. Figure 4D A comparison of the overall performance of the intrinsically stretchable OECT in the present invention and previously reported stretchable OECTs is shown, where the x-axis indicates the highest on / off ratio, the y-axis indicates the maximum allowed strain, and the z-axis indicates the maximum hole mobility of the channel. Figure 4EOptical microscopy images of PEDOT:PSS films fabricated on different stretchable substrates and at different strain values ​​(0%, 30%, and 50%, respectively) are shown.

[0026] Figure 5 is shown at low P O2 Intrinsically stretchable OECTs doped on substrates have g Significantly reduces I when increasing ds An overall diagram of the effect.

[0027] Fig. 6A and 6B The on / off ratios of OECT devices on different types of thermoplastic polyurethane (TPU) were compared. Fig. 6A Shown are transfer curves obtained from OECTs fabricated on three different types of TPU substrates at Vds = -0.4 V. TPU1 is provided with closely packed segments, TPU2 is a polyether based elastomer and TPU3 is a semipermeable TPU film. Figure 6B The on / off ratios of devices fabricated on three types of TPU substrates and the corresponding P O2 .

[0028] Fig. 7A and 7B The mobility of PEDOT:PSS channels on glass and low-PO2 TPU substrates was compared. Fig. 7A The results show that at different gate currents (I gs ) value, I on TPU substrate (left) and glass substrate (right) ds Apply a constant V of -0.2V ds The channel width is 5 mm and the channel length is 1.3 mm. Figure 7B I ds The derivative with respect to time is I gs The correlation of the function.

[0029] Fig. 8A and 8B The mobility of PEDOT:PSS channels on PDMS and TPU substrates was compared. Fig. 8A shows that in a series of I gs Stretchable OECTs applied to TPU (left) and PDMS (right) ds Apply a constant V of -0.2V ds The device had a channel width of 5 mm and a channel length of 1.3 mm. Figure 8B I ds The derivative with respect to time is I gs The correlation of the function.

[0030] Fig. 9 Transfer curves of rigid OECTs (left) and stretchable OECTs (right) with different geometries (width-to-length ratio, W / L) are shown. Vds is -0.4 V and the width of the device is fixed at 5 mm.

[0031] Fig.10 The transfer curve (left) and output curve (right) of the fully PEDOT:PSS-based stretchable OECT are shown.

[0032] Fig.11 Transfer curves of stretchable OECTs at different strain values ​​are shown. Fully stretchable OECTs were fabricated on TPU. Solid and stretchable gel was used as stretchable electrolyte. Liquid metal (eutectic gallium indium, EGaIn) was utilized to facilitate the probing of electrodes during strain testing.

[0033] Fig.12 The strain-insensitive characteristics of the stretchable OECT are shown. The left figure shows the transfer curve of the stretchable OECT device stretched between the 10th and 20th cycles, and the right figure is an enlarged view.

[0034] Fig.13 The maximum transconductance (g) of the stretchable OECTs after multiple strain (50%) cycles is shown. m ) changes.

[0035] Fig.14 is a comparison of channel mobility at different strain values.

[0036] Fig.15 is a comparison of the resistance change (R / R0) of PEDOT:PSS films fabricated on different stretchable substrates.

[0037] Fig.16A and 16B Thickness-dependent stretchability curves of PEDOT:PSS films on TPU substrates are shown. Fig.16A Optical images of PEDOT:PSS films of different thicknesses at different strain values ​​(0%, 30%, and 50%, respectively) are shown. The thickness was controlled by changing the spin coating from 500×30s rpm to 3000×30 rpm. Fig. 16B The strain-resistance curves of PEDOT:PSS films with different thicknesses are shown. The dimensions of the PEDOT:PSS films used were 1 cm in length and 0.5 cm in width. The resistance was measured by using liquid metal as a detection electrode.

[0038] Fig.17A and 17B The water stability of PEDOT:PSS films on TPU with and without the addition of GOPS is shown. Fig.17Ais a comparison of the resistance change of PEDOT:PSS film under strain before and after adding GOPS. Fig. 17B The enhancement of water stability by the addition of GOP is shown. The samples (with or without the addition of GOPS) were soaked in water for up to 7 days. The width of the samples was 1 cm and the length was 0.5 cm.

[0039] Fig.18 The cyclic stability of the electromechanical properties of the PEDOT:PSS film on TPU is shown. The left image shows the current change from 0% to 30% recorded for 150 strain cycles, and the right image is a magnified image from 140 to 150 strain cycles. I0 represents the initial current, and I represents the current recorded in real time.

[0040] Fig.19A and 19B Mechanical curves of TPU and PDMS elastomers are shown. Fig.19A Stress-strain curves of TPU and PDMS elastomers are shown. Fig.19B is a comparison of the Young's Modulus of PDMS and TPU, where the data is directly from Fig.19A Extracted from.

[0041] Fig. 20 Results of finite element analysis (FEA) are shown. Stress distribution of PEDOT:PSS films on TPU substrate (left) and PDMS substrate (right) under 30% strain is shown.

[0042] Fig.21 Shows that at a given V g Effect of oxygen permeability of elastomeric substrate under pulse on I in stretchable OECTs ds The impact of nonlinear response.

[0043] Fig.22A The transient responses of PEDOT:PSS OECTs on PDMS substrates with different oxygen permeabilities by changing the mixing ratio between the monomer and the curing agent are shown. Fig. 22B Compared with different V g Value from Fig.22A The decay time τ of the extracted pulse.

[0044] Fig.23A is a diagram of the setup for electrochemical analysis. Fig. 23B CV curves of PEDOT:PSS thin films on PDMS substrate with different oxygen permeabilities controlled by adjusting the mixing ratio are shown.

[0045] Fig.24A Shown is the use of OECTs to simulate the synaptic behavior of neurons. Fig. 24BThe results of tuning the short-term memory behavior of stretchable OECTs by adjusting the oxygen permeability of the substrate are shown. Longer retention times of Ids are obtained by reducing the oxygen permeability from about 1800 barrer in PDMS to about 1 barrer in TPU.

[0046] Fig.25 The electrochromic phenomenon of PEDOT:PSS on substrates with different oxygen permeabilities is shown, where the oxygen permeability of TPU is about 1 Barrer and the oxygen permeability of PDMS is about 600 Barrer. DETAILED DESCRIPTION

[0047] In detail, turning to the accompanying drawings, Figure 1A A device 100 equipped with a stretchable OECT according to an embodiment is depicted. The device 100 includes a source electrode 10, a drain electrode 20 and a gate electrode 30 and a channel 40. The device is positioned on a substrate 50, which is a stretchable substrate with low oxygen permeability. A stretchable solid electrolyte 60 is cast on the gate electrode 30 and the channel 40.

[0048] In one embodiment, the stretchable substrate 50 is a stretchable elastomeric substrate. Specifically, the substrate 50 can be thermoplastic polyurethane; however, other low oxygen permeability substrates can also be used. Such substrates should be stretchable to at most 150% of their original length and have an oxygen permeability of less than 10 Barrer.

[0049] In another embodiment, the source electrode 10, the drain electrode 20, the gate electrode 30 and the channel 40 are all formed of a stretchable substance. Specifically, the source electrode 10, the drain electrode 20, the gate electrode 30 and the channel 40 are all formed of a thin film containing a poly(3,4-ethylenedioxythiophene)-poly(styrene-sulfonic acid) mixture. In such a mixture, the ratio of poly(3,4-ethylenedioxythiophene) to poly(styrene-sulfonic acid) can be 1:1 to 1:3. The poly(3,4-ethylenedioxythiophene)-poly(styrene-sulfonic acid) mixture is formed by first stirring the PEDOT:PSS aqueous suspension for 3 minutes and mixing with glycerol (5 v / v.%) and dodecylbenzenesulfonic acid (DBSA) (0.1 V / V.%) using a vortex mixer to increase the membrane conductivity and promote the wetting properties of the membrane on the substrate, respectively, and filtering the mixed suspension with a polytetrafluoroethylene membrane (pore size 0.45 μm) to remove aggregates for further use. In another embodiment, the poly(3,4-ethylenedioxythiophene)-poly(styrene-sulfonic acid) mixture may further include a (3-glycidyloxypropyl)trimethoxysilane crosslinker.

[0050] In yet another embodiment, the device 100 may further include a surfactant. Specifically, the surfactant may be dodecylbenzenesulfonic acid.

[0051] In other embodiments, the solid electrolyte 60 can be a stretchable ion gel. Specifically, the stretchable ion gel can be a polyacrylamide-based gel. The polyacrylamide-based gel can be synthesized by: (i) dissolving 15.5 w / w% acrylamide powder in 16 ml of deionized water; (ii) adding 0.01875% w / w% N,N'-methylenebisacrylamide as a crosslinker; (iii) adding 1.2 w / w% ammonium persulfate as a photoinitiator; (iv) adding 10 w / w% NaCl to improve ionic conductivity; (v) adding N'-tetramethylethylenediamine at a weight of 0.025 weight% of acrylamide as a crosslinking promoter; (vi) transferring the above precursor solution to a dish and exposing it to a UV lamp (365 nm, 5 mW cm -2 ) and (vii) obtaining a stretchable gel after solvent exchange by immersing the cured hydrogel in a bath consisting of 85% glycerol, 5% water and 10% NaCl for 2 days.

[0052] In another embodiment, when the device 100 is stretched to 110% of its original length, the mobility of the transistor of the device 100 is reduced by less than 10%. In yet another embodiment, when the device 100 is stretched to 150% of its original length, the mobility of the transistor of the device 100 is reduced by less than 25%.

[0053] On the other hand, a method for preparing the device 100 is also disclosed. First, a stretchable film is formed into a planar gate electrode 30 parallel to the channel 40. The source electrode 10 and the drain electrode 20 made of a stretchable material are patterned onto a stretchable substrate 50. A stretchable layer 70 is cast on the sub-pattern. The film is annealed to obtain the channel 40; specifically, the annealing temperature is 80 to 120°C and the duration is 15 to 30 minutes. Finally, a stretchable solid electrolyte 60 is cast on the channel 40 and the gate 30.

[0054] In one embodiment, the stretchable film forming the source electrode 10, the drain electrode 20, the gate electrode 30, the channel 40 and the stretchable layer 70 is formed of a mixture of poly(3,4-ethylenedioxythiophene) and poly(styrene-sulfonic acid), wherein the ratio of poly(3,4-ethylenedioxythiophene) to poly(styrene-sulfonic acid) may be 1:1 to 1:3. In another embodiment, the poly(3,4-ethylenedioxythiophene)-poly(styrene-sulfonic acid) mixture may further contain a crosslinking agent. The crosslinking agent may be (3-glycidyloxypropyl)trimethoxysilane; however, other crosslinking agents may be used.

[0055] In one embodiment, the stretchable substrate 50 is a stretchable elastomeric substrate. Specifically, the substrate 50 can be thermoplastic polyurethane; however, other low oxygen permeability substrates can also be used. Such substrates should be stretchable to at most 150% of their original length and have an oxygen permeability of less than 10 Barrer.

[0056] In other embodiments, the stretchable solid electrolyte 60 may be a stretchable ion gel. Specifically, the stretchable ion gel may be a gel based on polyacrylamide.

[0057] In yet another embodiment, the device 100 may further include a surfactant. Specifically, the surfactant may be dodecylbenzenesulfonic acid. Examples: Example 1: Study on different P O2 Value of the on / off ratio of the elastic body

[0058] Compared with rigid devices, PEDOT:PSS OECTs fabricated on stretchable elastomers have always suffered from a low on / off ratio. Considering that the on / off ratio of OECTs is mainly determined by the off-state current (i.e., the dedoping level of the PEDOT:PSS channel) Figure 1A ), we assume that there are hidden parameters in the stretchable substrate that can prevent channel dedoping, and oxygen permeability is the main hidden parameter. Since oxygen molecules significantly affect the redox process, and stretchable elastomers have more pores and a larger free volume than rigid substrates, providing accessible pathways for oxygen molecules, which increases the oxygen content and prevents PEDOT from dedoping. + Dedoping at the substrate / channel interface. Therefore, the oxygen content in the stretchable elastomer can be up to ten times that in the electrolyte, significantly affecting the on / off ratio.

[0059] In order to verify the hypothesis, PDMS elastomers with different oxygen permeabilities were prepared by controlling the mixing ratio ( Figure 1C ). Before preparing the PDMS substrate, a hexadecyltrimethylammonium bromide (CTAB) solution (0.005 M) was prepared and then spin-coated on a glass slide as an anti-sticking layer to facilitate PDMS peeling at the end of the process. In the next step, the base and curing agent of the PDMS are mixed. In order to obtain PDMS with different oxygen permeabilities, the mixing ratio between the base and the curing agent ranges from 5:1 (low permeability) to 20:1 (high permeability). After removing bubbles under vacuum, the premixed slurry is spin-coated on a glass substrate at 500 rpm for 10 seconds and at 1000 rpm for 30 seconds. Afterwards, the sample is cured in an oven at 80 ° C for 30 minutes. Finally, the PDMS substrate is separated from the glass slide for future use.

[0060] The OECTs are fabricated by first patterning the source and drain electrodes, followed by a baking process at 120° C. Subsequently, a layer of PDMS is pasted on top of the source and drain electrodes for insulation.

[0061] Figure 1D The on / off ratio and P are shown in O2 According to the hypothesis, P O2 Reducing the off-state current from about 1700 Barrer to about 100 Barrer can significantly reduce the off-state current ( Figure 1C ). For example, in P O2 For a substrate of about 1700, the off-state current is about 10-1mA, and when P O2 When it drops to about 100, the value drops to 5×10 -3 mA( Figure 1C ). Therefore, the on / off ratio increases dramatically from 10 to 300 ( Figure 1D )[(I ds (V g =0V) / I ds (V g =0.8V)]. Example 2: Comparison of different P O2 The performance of transistors doped on the substrate

[0062] To further validate the results, devices were subsequently fabricated on different types of elastomers, including PDMS, styrene-butadiene rubber (SBR), ethylene propylene diene monomer (EPDM), poly(styrene-ethylene-butylene-styrene) (SEBS), ethylene vinyl acrylate (EVA), and thermoplastic polyurethane (TPU) ( Figure 2A ). The manufacturing conditions are carefully controlled so that P O2 Become the main variable parameter.

[0063] The elastic substrate was manufactured by a typical solution casting process. TPU particles were dissolved in dimethylformamide (DMF) at a heating temperature of 80°C, and styrene-ethylene-butylene-styrene block copolymer (SEBS) and styrene-butadiene rubber (SBR) were dissolved in toluene. EVA particles were dissolved in THF at room temperature.

[0064] For all elastomer solutions involved, 10 w / w% solutions were prepared by mixing 1 g of elastomer with 9 g of the corresponding solvent. After complete dissolution, the obtained solutions were cast on 2.5 cm×7.5 cm glass slides and elastic substrates were obtained after drying at room temperature in a fume hood overnight.

[0065] The fabrication method of OECT is through patterning the source and drain electrodes, followed by a baking process at 120° C. Subsequently, a layer of PDMS is pasted on top of the source and drain electrodes for insulation.

[0066] In order to minimize the differences caused by the different film-forming abilities of PEDOT:PSS on different substrates, the PEDOT:PSS film was prepared by first spin-coating the mixture suspension on a glass slide and then transferring it to the target substrate with a water-soluble tape. To confine the electrolyte, a hole was then defined with a hollow cylinder (10 mm in diameter) on the top of the channel. A commercial Ag / AgCl electrode was then used as the gate electrode, and a 0.1 M NaCl solution was filled in the hole as the electrolyte. This preparation method

[0067] Figure 2B The on / off ratio of different substrates and P are shown in O2 The correlation between the values ​​is consistent with the above results. O2 There is an inverse relationship between the value and the on / off ratio. That is, with lower P O2 In particular, in substrates with extremely low P values ​​of about 1, a high on / off ratio is often obtained. O2 The devices fabricated on the TPU substrate show about 10 4 This results in a record high on / off ratio, which is comparable to the best values ​​reported for rigid devices of the same size.

[0068] By comparing the O2 The on / off ratio of the device fabricated on the TPU substrate ( Fig. 6A and 6B ), further verified the above results. Example 3: Benchmarking the performance of stretchable OECT devices versus OECT devices on rigid substrates

[0069] Further studies were conducted to compare the overall performance of stretchable substrates designed to have the same dimensions and use the same electrolyte, making the substrate the main variable parameter.

[0070] Figure 3A and 3B The results are summarized in . As shown, both devices show similar output and transfer curves. From the transfer curves, the corresponding on / off ratios are extracted. Figure 3C As shown, both devices show comparable on / off ratios regardless of the W / L ratio. When the W / L ratio increases to 50, the on / off ratio reaches a high value of about 104. A transconductance (gm) of 15 mS (at Vg = 0.1 V) was further extracted from those stretchable devices. As far as we know, for devices with low P O2The intrinsically stretchable PEDOT:PSSOECTs of the present invention are compared with rigid devices fabricated on glass substrates, which have the highest gm reported so far. To this end, their steady-state performances, including output curves and transfer curves, are first compared. These devices

[0071] Next, the transient behaviors of stretchable OECTs and rigid OECTs were compared, including their transient response and frequency response curves. For both devices (W / L = 50), similar transient responses ( Figure 3D ) and frequency response ( Figure 3E ) curve. gm maintains a stable value up to 100 Hz, comparable to a rigid device of the same geometry.

[0072] According to the Malliaras-Bernards model, the response of an OECT can be understood by considering the OECT to consist of two circuits: an ionic circuit, in which ions are transported between the electrolyte and the channel; and an electronic circuit, in which holes are transported in the PEDOT:PSS channel between the source and the drain. The ionic circuit is controlled by the ionic species and the interface between the electrolyte and the channel. The latter can be estimated by driving the OECT with a constant gate current and simultaneously measuring the variation of the source-drain current with respect to the response time, and the mobility of PEDOT:PSS on soft and rigid substrates can be calculated by the following equations (1) to (3): τ e =-L 2 / uV ds (3) Where t is the time, I ds Is applied I gs The previous source-drain current, f, is a proportionality constant that accounts for the spatial non-uniformity of the dedoping process, e is the electron transit time, L is the channel length of the OECT (1.3 mm), and V ds is the source-drain voltage (-0.2 V). u represents the hole mobility of the PEDOT:PSS channel. According to equations (1) and (2), we can Fig. 6A I ds The electron transit time is calculated from the linear transient response range of . Subsequently, the mobility (u) can be extracted according to equation (3).

[0073] The extracted mobility ( Fig. 7A , 7B , 8A and 8B) up to about 1.1 cm 2 V -1 s -1 , and the value of the rigid device (about 1.2cm 2 V -1s -1 )quite. Example 4: Study on the durability of stretchable OECT devices under strain

[0074] After confirming the high performance, the durability of the device under strain was investigated. To make the device fully stretchable, a stretchable PEDOT:PSS film was used as a planar gate electrode ( Figure 4A ).

[0075] In this example, the PEDOT:PSS film is used as a planar gate electrode parallel to the channel. Two parallel PEDOT:PSS strips are patterned onto a TPU substrate using a shadow mask. The shadow mask is made of polyamide tape by laser cutting. The mask is attached to the TPU substrate and then the PEDOT:PSS suspension is spin coated (500rpm for 15 seconds, then 1500rpm for 45 seconds) on top of the surface. After peeling off the shadow mask, the patterned PEDOT:PSS channel is obtained after baking the film at 100°C for 20 minutes. Then, a stretchable ion gel is used as a stretchable electrolyte by casting on the channel and the gate. Liquid metal eutectic gallium indium (EGaIn) is used to exploit the detection of stretchable electrodes under strain testing.

[0076] Before strain testing, the device was cyclically stretched to 50% strain three times to stabilize the conductance of the channel ( Fig.11 ).

[0077] Then, Figure 4B and 4C The transfer curves obtained during the strain testing are shown in FIG.

[0078] In general, these transfer curves show little variation at different strain values ​​or increasing strain cycles ( Fig.12 ).

[0079] For g m The same trend was recorded ( Fig.13 ), demonstrating the robustness of the device.

[0080] Before 15% strain, the mobility remained at about 1 cm 2 V -1 s -1 The mobility is shown to decrease slightly to 0.85 cm at 50% strain. 2 V -1 s -1 ( Fig.14 ), which is attributed to the conductive PEDOT + Strain-induced expansion of the conjugated polymer, which suppresses the interchain hopping of holes.

[0081] exist Figure 4DThe overall performance of the stretchable OECTs is summarized in Table 1 below. Table 1: Benchmarking the performance of reported stretchable OECTs

[0082] In summary, the device shows a record high on / off ratio (about 10 4 ), high mobility (about 1cm 2 V -1 s -1 ) and stretchability (>50%). This is the first time that these high values ​​have been achieved in an intrinsically stretchable OECT. Example 5: Microscopic examination of stretched PEDOT:PSS film

[0083] Finally, the mechanism of the high intrinsic stretchability of the device is investigated by comparing optical microscopy images of PEDOT:PSS films at different strain values ​​( Figure 4E ).

[0084] It should be noted that the PEDOT:PSS film on the TPU substrate showed few cracks and maintained significant current at 50% strain, while the films on the other reference substrates showed significant cracks and exhibited considerable current loss at lower strain values ​​( Fig.15 ).

[0085] It is worth mentioning that the high intrinsic stretchability of PEDOT:PSS films is obtained without adding any plasticizers, which are required in all previous works.

[0086] When the film thickness is increased to 1 μm ( Fig.16A and 16B ) or add (3-glycidyloxypropyl)trimethoxysilane (GOPS) crosslinker ( Fig.17A and 17B ), the high stretchability of the film is maintained.

[0087] In addition, these films showed a smaller current loss under cyclic strain testing ( Fig.18 ).

[0088] The high intrinsic stretchability is attributed to the improved matching of Young's modulus between the substrate and the PEDOT:PSS film.

[0089] This conclusion was subsequently verified by finite element analysis (FEA) ( Fig.19A , 19B and 20), suggesting that the improved modulus matching of the two layers facilitates the dissipation of stresses and favors the formation of microcracks rather than large transverse cracks, thereby improving the intrinsic stretchability of the device.

[0090] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention. References [1] S. Zhang, E. Hubis, G. Tomasello, G. Soliveri, P. Kumar, F. Cicoira, "Chemistry of Materials" 2017, 29, 3126. [2] B. Marchiori, R. Delattre, S. Hannah, S. Blayac, M. Ramuz, Scientific reports, 2018, 8, 1. [3] W. Lee, S. Kobayashi, M. Nagase, Y. Jimbo, I. Saito, Y. Inoue, T. Yambe, M. Sekino, GGMalliaras, T. Yokota, "Science advances" 2018, 4, eaau2426. [4] S. Zhang, Y. Li, G. Tomasello, M. Anthonisen, X. Li, M. Mazzeo, A. Genco, P. Grutter, F. Cicoira, "Advanced Electronic Materials (Advanced Electronic Materials)" 2019, 5, 1900191. [5] N. Matsuhisa, Y. Jiang, Z. Liu, G. Chen, C. Wan, Y. Kim, J. Kang, H. Tran, H. C. Wu, I. You, Advanced Electronic Materials, 2019, 5, 1900347. [6] Y. Li, N. Wang, A. Yang, H. Ling, F. Yan, Advanced Electronic Materials, 2019, 5, 1900566. [7] T.D. N. Guyen, T.Q. Trung, Y. Lee, N.-E. Lee, Advanced Engineering Materials, 2021, 2100918.

Claims

1. A method for changing the electrochemical properties, electrochromic properties, nonlinearity and synaptic behavior of an electronic device, characterized in that: The method comprises: Providing an elastic substrate selected from one or more of an elastomer, a hydrogel, or an organic-inorganic hybrid material, the stretchable substrate having a selected oxygen permeability of 0.1 to 50 Barrer; and A stretchable redox active layer is formed on the substrate, the redox active layer comprising one or more of a conductive polymer, an organic molecule, or an organic-inorganic hybrid molecule.

2. The method according to claim 1, characterized in that: Further comprising depositing one or more electrodes on the elastic redox-active layer.

3. The method according to claim 1, characterized in that The electronic device is a bioelectronic device in the form of a bioelectrode, a wearable biosensor or a bioelectronic implant.

4. The method according to claim 1, characterized in that: The electronic device has the shape of a microwire, a macrowire, a micromesh, a macromesh, a film, a micro 3D structure and / or a macro 3D structure.

5. The method according to claim 1, characterized in that The stretchable substrate is selected from styrene-butadiene rubber, ethylene propylene diene monomer, poly(styrene-ethylene-butylene-styrene), ethylene vinyl acrylate and / or thermoplastic polyurethane.

6. A stretchable device equipped with an intrinsically stretchable organic electrochemical transistor, characterized in that: The stretchable device comprises: An OECT comprising a stretchable planar gate electrode, a source electrode, a drain electrode, and a channel each comprising a conductive polymer; a stretchable ion gel cast as a solid electrolyte on the channel and the gate; and a stretchable elastomeric substrate; wherein the width / length ratio of the OECT is 3.5 to 50; wherein the on / off ratio of the device is at least 10 3 ; The mobility of the device is at least 0.8 cm 2 V -1 s -1 ;and When the device is stretched to 150% of its original length, the current loss of the transistor is less than 10%.

7. The device according to claim 6, characterized in that The stretchable substrate is selected from an elastomer, a hydrogel or an organic-inorganic hybrid stretchable polymer.

8. The device according to claim 7, characterized in that The stretchable substrate is selected from styrene-butadiene rubber, ethylene propylene diene monomer, poly(styrene-ethylene-butylene-styrene), ethylene vinyl acrylate and / or thermoplastic polyurethane.

9. The device according to claim 6, characterized in that The device has the shape of a microwire, a macrowire, a micromesh, a macromesh, a film, a micro 3D structure and / or a macro 3D structure.

10. The device according to claim 6, characterized in that The conductive polymer is a mixture of poly(3,4-ethylenedioxythiophene) and poly(styrene-sulfonic acid).

11. The device according to claim 10, characterized in that The ratio of the poly(3,4-ethylenedioxythiophene) to the poly(styrene-sulfonic acid) is 1:1 to 1:

3.

12. The device according to claim 6, characterized in that The stretchable ion gel is a polyacrylamide-based gel.

13. The device according to claim 6, characterized in that The mobility of the transistor decreases by less than 10% when the device is stretched to 110% of its original length.

14. The device according to claim 6, characterized in that The mobility of the transistor decreases by less than 25% when the device is stretched to 150% of its original length.